(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: To assess the serum magnesium level of pregnant women with pre-eclampsia and eclampsia in Mymensingh Medical College & Hospital (MMCH). Materials and Methods: This descriptive cross-sectional study was carried out in the department of Obstetrics and Gynaecology of Mymensingh Medical College & Hospital (MMCH) and Prof. Muhammed Hossain Central Laboratory of Bangladesh Agricultural University (BAU). The serum magnesium level were estimated in 60 study subjects who were pregnant women with pre-eclampsia & eclampsia and of 60 control subjects who were the normotensive pregnant women by photometric test using xylidyl blue. Results: The mean (±SD) serum magnesium of the control and study group were (2.29 ± 0.28 mg/dl) & (1.84 ±0.26 mg/dl) respectively. The difference in serum magnesium level between the two groups was statistically highly significant (p=<0.001). In the study group the mean (±SD) serum magnesium level of the pre-eclamptic & eclamptic groups were (1.9150 ± 0.26 mg/dl) & (1.8063 ±0.25 mg/dl) respectively and the difference between them was also statistically significant (p=<0.05). Conclusion: From the result it could be concluded that hypomagnesaemia can be said to be one of the etiological factors in pre-eclampsia and eclampsia. Hence by estimating serum magnesium during antenatal period pre-eclampsia can be predicted and eclampsia can be prevented early. DOI: http://dx.doi.org/10.3329/bjog.v25i1.13725 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(1) : 15-19